Patterns of Enrollment and Engagement of Custodial Grandmothers in a Randomized Clinical Trial of Psychoeducational Interventions. Issue 2 (April 2016) - Smith, Gregory C.; Strieder, Frederick; Greenberg, Patty; Hayslip, Bert; Montoro‐Rodriguez, Julian
Abstract: Andersen's (2008) behavior model was used to investigate patterns of enrollment and treatment engagement among 343 custodial grandmothers who participated in a randomized clinical trial of three psychosocial interventions:(a) a behavioral parenting program, (b) a cognitive behavioral coping program, or (c) an information‐only condition. Treatment completion was superior to that typically found with birth parents, even though the grandmothers and their target grandchildren both had high levels of mental and physical health challenges. Compliance did not differ significantly by condition but was higher among grandmothers who self‐reported less positive affect, were older, and were using mental health professionals. Treatment satisfaction was highest in grandmothers who attended more treatment sessions, reported lower annual family income, had a health problem, and were using mental health professionals. The practice and policy implications of these findings are discussed, especially in terms of strategies for enhancing the engagement of custodial grandfamilies in future psychoeducational interventions.